Challenges in teaching English as a foreign language at schools in Poland and Turkey - Madalinska-Michalak, Joanna; Bavli, Buenyamin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
This paper reports on a qualitative case study that investigated the challenges faced by teachers who teach English as a foreign language at secondary schools in Poland and Turkey. A number of shared challenges affecting teachers in both Poland and Turkey were identified, despite the contrast between these educational contexts. These challenges included: students' motivation to learn; students' emotional inhibitions; teaching large classes; differentiation; the need for the quality in-service teachers' professional development; high teaching hours; provision of pre-service teacher education; attractiveness of the profession; and career-path incentives. Importantly, some of these challenges have not been highlighted in the literature to date. Other challenges are more localised, such as in-service professional development focused on developing teachers' competence in English language. The findings suggest that support provided for teachers of English must be flexibly aligned to local educational conditions as well as by evidence based strategies at national level.
Keywords: Challenges in teaching; English as a foreign language at school; Teacher education; Comparative study; Case study; PROFESSIONAL-DEVELOPMENT; EDUCATION; TEACHERS; LEARN; MATHEMATICS; MOTIVATION; Education & Educational Research